(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study evaluated consumer perceptions and market acceptability of Café de Maiz, an innovative, non-caffeinated corn-based coffee substitute produced by a social enterprise in Bay, Laguna. Utilizing a quantitative descriptive-evaluative design, data were gathered from 236 active coffee consumers selected through purposive and convenience sampling. The primary market demographic was identified as young adult females (18–25 years old) operating within a monthly allowance of ₱5,000–₱10,000. Descriptive analysis revealed strong overall market acceptability (x̄ = 3.10, SD = 0.84), driven primarily by promotional outreach and affordable pricing. Consumer perception was highly positive (x̄ = 3.11, SD = 0.82), with respondents valuing the beverage’s non-acidic properties and its support for local agricultural sustainability. One-Way ANOVA confirmed that market acceptability did not vary significantly across demographic segments (p > 0.05), indicating broad market appeal. Crucially, Pearson correlation analysis revealed a statistically significant, weak negative relationship between consumer perception and market acceptability (r = -0.1574, p = 0.0157). This finding highlights a distinct attitude-behavior gap: while consumers highly approve of the health and ethical benefits of corn coffee, their actual transactional engagement is constrained by operational barriers, primarily localized product availability (x̄ = 2.78) and deep-seated habitual preferences for commercial instant coffee (x̄ = 2.74). These results inform a strategic action plan focused on decentralized distribution, sensory-driven marketing, and value-added social advocacy to ensure enterprise sustainability.